(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The paper aims at illustrating the long-standing relationship between computational science and legal logic. In a highly discretionary area of human activity, such as criminal justice, artificial intelligence may appear a potential, effective solution to many recurrent conundrums. Moving from the current achievements of artificial intelligence, the paper offers a reflection on the possible role of these technologies, to understand how they can contribute to restore some effectiveness to a system that has lost, in the eyes of citizens, credibility and trustworthiness.